The Impact of COVID-19 Social and Public Activity Restrictions and Vaccination on Stock Returns in Indonesia - Willyandi Tairas; Sung Suk Kim (Budapest International Research and Critics University, 2022)
This study investigates both coronavirus disease (COVID-19) social and public activity restrictions as well as vaccination impact on stock returns of 351 listed companies in Indonesia. This study utilizes panel-data regression models, with the period of 2 March 2020 to 31 October 2021. Through this study, it is confirmed that lockdown did not significantly impact stock returns of listed firms. However, those listed firms’ stock returns were positively and significantly affected by vaccination.